2009
DOI: 10.1007/s15010-009-6002-9
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus anginosus (Streptococcus milleri Group) Pyomyositis in a 50-Year-Old Man with Acquired Immunodeficiency Syndrome: Case Report and Review of Literature

Abstract: We describe the first reported case of bacterial pyomyositis of the right thigh caused by Streptococcus anginosus (S. milleri group) in an HIV-infected patient. The clinical presentation was complicated by multiple ring-enhancing lesions detected on magnetic resonance imaging of the brain. Evaluation for central nervous system toxoplasmosis,syphilis, and cryptococcal infection was negative. Aggressive antibiotic therapy directed against S. anginosus and surgical debridement were limb salvaging. Clinicians shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The SAG are also medically important for their ability to cause suppurative infections and have been isolated from numerous body sites [10,11]. Of particular interest, SAG has been identified as the most common organism isolated from brain abscess [12,13], liver abscess [14] and empyema [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…The SAG are also medically important for their ability to cause suppurative infections and have been isolated from numerous body sites [10,11]. Of particular interest, SAG has been identified as the most common organism isolated from brain abscess [12,13], liver abscess [14] and empyema [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, they are capable of pyogenic infection and abscess formation. There are only three previous reported cases of S. milleri causing pyomyositis, [15][16][17] and all had risk factors (HIV or malnutrition). It is unclear why pyomyositis occurred in the reported child, who was immunocompetent and had no history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that the most frequently involved muscles were those around the quadriceps (26.3%), and the involvement of those around the shoulder including the rhomboideus muscle was found in only 7.9% of these patients. Pyomyositis can usually be a complication in immunocompromised conditions such as HIV and diabetes mellitus [ 1 3 ]. Our patient was not immunocompromised, because he was negative for HIV, his HbA1c level was within the normal range, and detailed examinations showed that he had no other diseases or symptoms.…”
Section: Discussionmentioning
confidence: 99%